Living with Addicted Men and Codependency: The Moderating Effect of Personality Traits - Panaghi, Leili (Addict Health, 2016)
BACKGROUND: This study aimed to determine the moderating effect of personality traits on the relationship between living with an addicted man and codependency. METHODS: We selected 140 women (70 wives of addicted men and 70 wives of non-addicted men) through convenience sampling method and asked them to complete Spann-Fischer Codependency Scale and NEO-Five Factor Inventory. FINDINGS: Codependency score was significantly higher among addicted men’s wives. In addition, for these women, there was a strong positive correlation between codependency and neuroticism as well. Multiple regression analysis confirmed the significant interaction effects of being an addict’s wife and personality traits of neuroticism, openness and agreeableness on codependency. CONCLUSION: Not all addicts’ wives experienced codependency; women with a high level of neuroticism and low level of openness and agreeableness were more vulnerable to the stress of living with an addict and to codependency.